1987
DOI: 10.1128/jcm.25.2.391-394.1987
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three immunofluorescence assays for culture confirmation and typing of herpes simplex virus

Abstract: (KL), were evaluated for the laboratory confirmation and typing of herpes simplex virus (HSV). Of 108 coded HSV slide preparations, run in parallel with each monoclonal-antibody set, 103 were equivalent by the immunofluorescence assays. Among the five discordant isolates, three (2.8%) did not type with the KL monoclonal antibodies and two (1.9%) false-positive results occurred with the Syva typing system. All of the HSV clinical isolates tested were correctly typed with the ENI indirect immunofluorescence anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The Syva typing kit resulted in three false-positive HSV-2 signals, giving the erroneous indication of dual HSV-1 and HSV-2 infections. Previous studies in our laboratory with the Syva kit incorrectly identified 2 of 108 positive specimens as dual infections (12). In reports of recent studies, Gleaves and coworkers (9, 10) reported a total of three dual isolates obtained with the Syva kit.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The Syva typing kit resulted in three false-positive HSV-2 signals, giving the erroneous indication of dual HSV-1 and HSV-2 infections. Previous studies in our laboratory with the Syva kit incorrectly identified 2 of 108 positive specimens as dual infections (12). In reports of recent studies, Gleaves and coworkers (9, 10) reported a total of three dual isolates obtained with the Syva kit.…”
Section: Discussionmentioning
confidence: 90%
“…Collection and transport of * Corresponding author. specimens to the laboratory have been described previously (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since several HSV-specific monoclonal antibodies (MAbs) have been shown to identify type-specific epitopes (2,5,11,17), these reagents have been used for type-specific antigen detection. However, the reported sensitivities and specificities for such reagents, including commercially available kits, have been found to vary among the assays in the range between 92 and 100% (4,6,7,17). This discrepancy may be explained by variability in the expression of different HSV proteins or intratypic variability of different epitopes within the same protein among the isolates (11).…”
mentioning
confidence: 99%
“…Direct identification of the virus can be done with cell culture, which is rather timeconsuming, electron microscopy, or antigen detection, quite often based on immunofluorescence techniques. [1][2][3][4][5][6][7] Reported sensitivities of different techniques vary widely. In addition, amplification of DNA from skin swabs by polymerase chain reaction (PCR) has also been established.…”
Section: Introductionmentioning
confidence: 99%